The Effect of Velocity Gradient and Camp Number on Solids Removal using Bio-Coagulant from Corbula faba Hinds Shells - Ardika Nurmawati; Kindriari Nurma Wahyusi; Retno Dewati; Jauhar Hilmy (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
process in water helps reduce solid content in water. The coagulant destabilizes water pollutants and helps flocs formation with the coagulation process. This paper studies the performance of chitosan bio-coagulant produced from Corbula faba Hinds shells. The velocity gradient and the Camp number of solids removal were also evaluated. The velocity and period of rapid mixing varied from 110 to 150 rpm, and the velocity gradient (G) was 181.2 to 288.5 s-1. The mixing period also ranged from 1 to 5 minutes. The highest TSS and TDS removal resulted in 140 rpm or 260.2 s-1 and 4 minutes of mixing. The residual TSS and TDS decreased with the increase of Camp Number until reaching a point and increased again afterward.